2009
DOI: 10.1007/s00423-009-0489-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care and emotional support from the inpatient cancer patient’s perspective

Abstract: Emotional support is a crucial part of patient satisfaction and should be provided by several members of the oncological team, especially the patients' physicians. In turn, it is crucial that medical professionals be equipped with good communication skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
4
27
0
3
Order By: Relevance
“…The better communication with primary caregivers could be an essential part of perceived social support among older people in Taiwan. This result is consistent with the results of the Singer et al.’s (2009) research, which reported that good communication skill affects patients’ emotional support. Therefore, medical professionals who have good communication skills are perceived as providing emotional support to patients.…”
Section: Discussionsupporting
confidence: 92%
“…The better communication with primary caregivers could be an essential part of perceived social support among older people in Taiwan. This result is consistent with the results of the Singer et al.’s (2009) research, which reported that good communication skill affects patients’ emotional support. Therefore, medical professionals who have good communication skills are perceived as providing emotional support to patients.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers investigated patients' perspectives on diverse aspects of care service: waiting time [20,21], interaction and interpersonal skills [21,22], professionalism [23,24], occupancy [25], patient preferences and expectations [26,27], coordination of care [22,28], education and information provision [22,29,30], emotional support [31,32], and quality of medical care [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Offers were accepted by more than 90% of the approached patients, a rate that far exceeds acceptance rates observed in outpatient samples [3,4,5,6,16,28]. There may be several reasons for this divergence: hospitalised cancer patients have been found to suffer from particularly severe distress [9,10]; bedside counselling means less expenditure of time and effort than appointments at external psycho-oncology services, a point that may be particularly relevant for cancer patients many of whom are frail; and moreover, personal invitations by the counsellors themselves may lower the threshold for counselling.…”
Section: Discussionmentioning
confidence: 99%
“…While a growing body of research has investigated the impact of distress screening in cancer outpatient settings [3,4,5,6,7,8], research on distress screening in cancer inpatients has only just begun. Evidence of particularly high levels of emotional distress [9,10] and high rates of mental disorders [11] in hospitalised cancer patients suggests that distress screening may be especially relevant in an inpatient setting. In an Australian study, distress screening increased inpatient referrals to psychosocial services [12].…”
Section: Introductionmentioning
confidence: 99%